Halalan 2022 an audience analysis on the perception of first-time voters toward election campaign advertisements on Youtube - Macariola, Samantha Russell P.; Olvis, Sophia Marie T.; Sarita, Rhaiza Lynn E. (College of Communication, Art, and Design , University of the Philippines Cebu, 2023)
Youtube advertisements have now become a political tool for candidates in displaying their political campaigns. The goal of this research is to explore the influence of Youtube campaign ads and how it affects the voting preferences of first-time voters during the 2022 National elections in the Philippines. Various factors have affected the voting choices of first-time voters. However, there is a lack of resources that analyzes the effectiveness of Youtube ads in the Philippines. Cultivation theory, Agenda-Setting Theory, as well as the Cognitive Dissonance Theory, are utilized to back up and analyze the data collected. The research utilizes a five-point Likert scale, conducting a survey of 190 Filipino first-time voters who are students of Cebu Normal University, University of the Philippines - Cebu, and Cebu Technological University. The research findings demonstrate the perception of the respondents on the candidates and how it affected their voting choices. Findings show that the frequency, as well as the campaign messages, hold an impact on altering their voting choices. However, their perception of the qualities of the candidates is consistent before and after being exposed to the ads, thus it does not affect their voting choices.